FORMATION OF PROFESSIONAL CULTURE IN PHYSICAL EDUCATION COACHES - baxromov, otabek; Abdushukurov, Sultanbek (Физико-технологического образование, 2024)
This article reveals the opportunities for future physical education teachers to form a professional culture. The article also describes the situations that athletes should pay attention to in physical education classes, the integral connection between physical culture and aesthetic education. A look at the history of sports and physical education. The article analyzes the principles that are important for athletes